Secured cloud computing for medical data based on watermarking and encryption. Issue 5 (1st September 2018) - Boussif, Mohamed; Aloui, Noureddine; Cherif, Adnene
Abstract : In this study, the authors propose a hardware implementation of a local cloud for storing, sharing and archiving patient's folders (health report and medical imaging) based on raspberry Pi card and a local cloud (hard disc) while exchanging with other distant public cloud (google drive, azure cloud, …). Securing the medical data is ensured by a proposed encrypting method for the watermarked digital imaging and communications in medicine imaging which contains the patient information (the watermark) and the advanced encryption standard is used to crypt the text files (health reports). The imaging encryption method is based on the exoring of the i th block to be encrypted and the i th block key. The watermarking method is based on the insertion of the watermark in the least significant bit. Finally, encryption and watermarking keys are encrypted and stored in the database. A real‐time implementation on raspberry Pi and android smartphone is proposed for the whole system using, respectively, PHP and android studio. Experimental results demonstrate that the proposed security method is robust against different types of attacks and can achieve high security with a good performance.